The prevalence of premenstrual syndrome symptoms and associated factors among female medical students at Al-Andalus University: a cross-sectional study - Salman, Safa K.; Esmandar, Dina I.; Sarem, Enana K.; Attaf, Ram F. (International Journal of Scientific Reports, 2024)
Background: Premenstrual syndrome (PMS) is a menstrual disorder defined as a cluster of various physical, emotional, and behavioural symptoms that negatively affect women’s quality of life. This cross-sectional study aimed to assess the prevalence of common PMS symptoms and determine their association with body mass index (BMI), lifestyle, dietary habits, perceived stress, menstrual flow, family history and family income among medical students at Al-Andalus University in Syria. Methods: A sample of 205 female students were interviewed and filled out a questionnaire. All data were coded and entered into excel (Microsoft 2019). One-way analysis of variance (ANOVA) and Chi-square tests were used to evaluate the association between PMS symptoms and the studied factors. Results: The most frequently reported PMS symptoms were anxiety (80%), bloating (74.6%), and breast tenderness (62.9%). Our study found a significant association between weight gain pre-menstruation and BMI (p=0.02). A significant relationship was found between increased premenstrual consumption of sweets and both breast tenderness and bloating (p=0.01). Daily consumption of coffee was significantly correlated with weight gain and headaches (p<0.001). This study found a significant relationship between smoking cigarettes and abdominal and back pain (p=0.04, p=0.02, respectively). Smoking shisha was significantly associated with fatigue and bloating (p=0.01, p<0.001, respectively). A significant relationship was found between menstrual flow and both abdominal pain and headaches (p=0.01, p=0.02, respectively). Conclusions: A high prevalence of PMS symptoms was reported in Al-Andalus University female medical students. Additionally, this study found multiple significant associations between BMI, dietary habits, lifestyle, menstrual flow and the severity of symptoms.